2023
DOI: 10.1186/s12967-023-04612-7
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Mendelian randomization analysis of the genetic association between primary lung cancer and colorectal cancer

Zhihan Xiao,
Zichen Wang,
Tongyu Zhang
et al.

Abstract: Background With the development and popularization of low-dose chest CT technology, the diagnosis and survival rates of patients with early lung cancer (LC) have significantly improved. The occurrence of colorectal cancer (CRC) as the second primary cancer (SPC) in primary lung cancer (PLC) survivors has become an essential factor affecting the prognosis of early LC. This study explored the potential association between PLC and CRC genetically, laying a foundation for developing SPC-CRC prevent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This is due to their increased susceptibility to developing CRC. Previously, our team of researchers successfully established a noteworthy genetic correlation between primary lung cancer and CRC through MR method (25). However, in this study, our research team did not find a statistically significant association between PBC and CRC using MR approach.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This is due to their increased susceptibility to developing CRC. Previously, our team of researchers successfully established a noteworthy genetic correlation between primary lung cancer and CRC through MR method (25). However, in this study, our research team did not find a statistically significant association between PBC and CRC using MR approach.…”
Section: Discussionmentioning
confidence: 62%
“…To ensure the validity of IVs, the fulfillment of three assumptions is necessary: (a) the independence of the IVs from the outcome should be taken into account when evaluating the exposure, which is restriction; (b) the correlation between the IVs and the exposure is necessary, which is commonly referred to as the "relevance" assumption; and (c) the independence of the IVs from any potential confounding factors, whether observed or unobserved, should be ensured (referred to as the assumption of "exchangeability") (22,23). Therefore, genetic IVs for overall BC, ER-BC, ER+ BC, overall CRC, colon cancer, rectal cancer, left CRC and right CRC were constructed according to the following criteria (24,25): (a) LD, linkage disequilibrium among IVs is measured using the r 2 statistic, with a threshold of less than 0.001 within a window size of 500 kb (Genetic variants in close genomic regions have a tendency to co-inherit, which is referred to as LD. When the presence of LD is observed alongside genetic variants, the information provided by each variant does not exist in isolation from one another.…”
Section: Selection Of Ivsmentioning
confidence: 99%
“…Subsequently, we clumped the selected SNPs with an r 2 = value of 0.001 and a distance of 10,000 kbto minimize the impact of linkage disequilibrium on the results (Chen et al, 2023). Additionally, a minor allele frequency (MAF) > 0.01 (mutations present in >1% of the population) was required (Xiao et al, 2023). The variation explained by each genetic instrument was determined using the following formula: 2 × EAF × (1 − EAF) × beta 2 , where EAF is the effect allele frequency and beta is the estimated effect.…”
Section: Selection Of Ivsmentioning
confidence: 99%
“…Since SNPs are formed during embryonic development and are independent of the environment and other acquired factors, the MR design provides a randomization procedure that also minimizes the interference of residual confounding and reverse causation [ 11 ]. In recent years, with further exploration of MR research methods, it has become increasingly confirmed as an ideal way to study and the pathogenic association between two complex diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%